Quantification of antibiotic resistance genes and mobile genetic in dairy manure - Yi Wang; Pramod Pandey; Colleen Chiu; Richard Jeannotte; Sundaram Kuppu; Ruihong Zhang; Richard Pereira; Bart C. Weimer; Nitin Nitin; Sharif S. Aly (PeerJ, 2021)
Background Antibiotic resistance genes (ARGs) are considered to be emerging environmental contaminants of concern potentially posing risks to human and animal health, and this research studied the prevalence of antimicrobial resistance in dairy manure. Methods This study is focused on investigating prevalence of ARGs in California dairy farm manure under current common different manure management. A total of 33 manure samples were collected from multiple manure treatment conditions: (1) flushed manure (FM), (2) fresh pile (FP), (3) compost pile (CP), (4) primary lagoon (PL), and (5) secondary lagoon (SL). After DNA extraction, all fecal samples were screened by PCR for the presence of eight ARGs: four sulfonamide ARGs (sulI, sulII, sulIII, sulA), two tetracycline ARGs (tetW, tetO), two macrolide-lincosamide-streptogramin B (MLSB) ARGs (ermB, ermF). Samples were also screened for two mobile genetic elements (MGEs) (intI1, tnpA), which are responsible for dissemination of ARGs. Quantitative PCR was then used to screen all samples for five ARGs (sulII, tetW, ermF, tnpA and intI1). Results Prevalence of genes varied among sample types, but all genes were detectable in different manure types. Results showed that liquid-solid separation, piling, and lagoon conditions had limited effects on reducing ARGs and MGEs, and the effect was only found significant on tetW (p = 0.01). Besides, network analysis indicated that sulII was associated with tnpA (p < 0.05), and Psychrobacter and Pseudomonas as opportunistic human pathogens, were potential ARG/MGE hosts (p < 0.05). This research indicated current different manure management practices in California dairy farms has limited effects on reducing ARGs and MGEs. Improvement of different manure management in dairy farms is thus important to mitigate dissemination of ARGs into the environment.